2020
DOI: 10.1097/hjh.0000000000002398
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to antihypertensive medications is related to pill burden in apparent treatment-resistant hypertensive individuals

Abstract: Objective: Non-adherence to medication is present in ≥50% of patients with apparent treatment resistant hypertension. We examined the factors associated with non-adherence as detected by an LC-MS/MS based urine antihypertensive drug assay.Methods: All urine antihypertensive test results, carried out for uncontrolled hypertension (BP persistently >140/90 mmHg) between January 2015 and December 2016 at a single toxicology laboratory were analysed. Drugs detected were compared to the antihypertensive drugs prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 59 publications
1
27
2
2
Order By: Relevance
“…Pill burden is a well-recognized issue in patients with hypertension that is associated with nonadherence to medications and poor blood pressure control. 21,22 This study showed that preoperative MRA was associated with a reduction in the number of antihypertensive medications and potassium supplements. Immediately before adrenalectomy, patients who were pretreated with MRA took a median of one antihypertensive medication and no potassium supplements.…”
Section: Resultsmentioning
confidence: 90%
“…Pill burden is a well-recognized issue in patients with hypertension that is associated with nonadherence to medications and poor blood pressure control. 21,22 This study showed that preoperative MRA was associated with a reduction in the number of antihypertensive medications and potassium supplements. Immediately before adrenalectomy, patients who were pretreated with MRA took a median of one antihypertensive medication and no potassium supplements.…”
Section: Resultsmentioning
confidence: 90%
“…RDN has been shown to lower BP compared to sham control in both the presence and absence of concomitant drug therapy. Thus, RDN-induced BP reductions are not affected by drug adherence, which is a primary weakness of medication therapy [76,77] . This allows for 24-hour BP control, including at night and early in the morning when the antihypertensive effect of the medication is likely to wear off due to the time course of drug ingestion [78] and pharmacokinetics [2] .…”
Section: Twenty-four-hour Bp Lowering and Mechanisms Of Cardiovascula...mentioning
confidence: 99%
“…Thus, RDN-induced BP reductions are not affected by drug adherence, which is a primary weakness of medication thera-py. [76,77] This allows for 24-hour BP control, including at night and early in the morning when the antihypertensive effect of the medication is likely to wear off due to the time course of drug ingestion [78] and pharmacokinetics. [2] Initially, it was thought that the SYMPLICITY HTN-3 trial failed to prove the antihypertensive effect of RDN.…”
Section: Twenty-four-hour Bp Lowering and Mechanisms Of Cardiovascula...mentioning
confidence: 99%
“…This is especially so in those who are on multiple anti-hypertensive and other medications. Urine antihypertensive drug monitoring may help management of these individuals [ 130 ]. Therefore, it is important to assess adherence especially in those not achieving blood pressure control despite taking 3 or more antihypertensive agents in optimum doses.…”
Section: Introductionmentioning
confidence: 99%